Revisiting non-fungible token (NFT) research trends: a bibliometric study and future research directions - Mahir Pradana; Cheah Wai Shiang; Karmilah Binti Abdullah; Marheni Eka Saputri; Farizka Shafa Nabila (Cogent Business & Management)
Non-fungible token (NFT) is a relatively new and developing trend in digital finance research that is fundamentally transforming the process of trading digital assets. The objective of this study is to present a concise overview and analysis of current research trends regarding NFT, with the intention of providing researchers with a framework for guiding future investigations in this field. In order to give researchers a framework for directing future studies in this area, the study objective is to provide a succinct review and analysis of current research trends. The objective of the study is to present a concise overview and analysis of current NFT research trends. We started by arranging framework of bibliometric study, setting appropriate keywords and operating the software. In the process, this study thoroughly examined 99 academic publications about NFTs that were listed in the Scopus database between 2009 and 2024 using VOSviewer. Our research shows that the analysis identifies four separate research clusters with a focus on digital economy, security, connections with other blockchains, and intellectual property. We conclude by making recommendations for the future based on the trends and gaps found in this bibliometric review.